Desain Sistem Pakar untuk Kontrol Kualitas Pakan - E Trisyulianti; H Hardjomidjojo; Y Arkeman; A Saefuddin (Media Peternakan, 2005)
The objective of feed production process is to generate high quality of feed with parameters, such as good physical, nutrition characteristics, continuous, palatability and safety. It is needed to support the optimum performance of production process. The general objective of this research was to study quality control system and application of quality management in feed production industry. The objective in this research was to design an expert system for feed quality control based on basic knowledge through knowledge acquisition. Model was designed through two steps, i.e. (1) preparation, and (2) development. System development consisted of (a) basic knowledge development in knowledge acquisition, knowledge conceptualization, and knowledge representation, (b) development of inference mechanism, (c) coding, and (d) verification. The Expert System showed that if data out of control, then process was on uncontrollable condition. The Expert System would interpret the causes and recommend the solution that should be done by supervisors/operators. Key words : expert system, feed, quality, process